Influence of Service Quality and Trust in Customer Satisfaction of Mobile Banking Users - Yuni Fahmi Pratiwi; Dahlia Pinem; Yuliniar Yuliniar (Journal of Economics, Business, and Government Challenges, 2022)
This research is a quantitative study entitled “The Influence of Service Quality and Trust on Customer Satisfaction of users Mobile Banking at Bank BCA”. This research is useful for knowing, analyzing and proving the effect of service quality and trust on customer satisfaction. The problem from this research is the use of transactions mobile banking which ranks first compared to other conventional banks, but this is not in line with the increasing number of complaints from BCA bank customers every year. This is also not commensurate with the vision and mission of Bank BCA which always strives to improve quality services and maintain customer trust and expectations and desires. This study uses a sample of users mobile banking BCA Bank in Jakarta where researchers use technical techniques non- probability sampling, namely purposive sampling as much as 70 respondents. Data collection is done through google form by distributing it through social media (WhatsApp, Line, Instagram, and Facebook). In the analysis using multiple regression techniques with descriptive analysis methods and inferential analysis and data processing using IBM SPSS Statistic v.25 with a significant level of 10% (0.1). The test results obtained (1) individual service quality has a significant effect on customer satisfaction (2) individual trust does not have a significant effect on customer satisfaction (3) service quality and trust jointly have a significant effect on customer satisfaction. Customer satisfaction is influenced by 58.2% by service quality and trust.